IGNORING PSYCHOMETRIC PROBLEMS IN THE STUDY OF GROUP DIFFERENCES IN COGNITIVE TEST PERFORMANCE. Issue 6 (17th July 2018) - Wicherts, Jelte M.
Summary: In a recent study, te Nijenhuis et al . (2017) used a version of Jensen's method of correlated vectors to study the nature of ethnic group differences on Raven's Progressive Matrices test. In this comment, the author points out that this method has been shown to be psychometrically inappropriate in studying group differences in performance on dichotomous (correctly or incorrectly scored) items. Specifically, the method uses item statistics like the item-total correlation that necessarily differ across groups differing in ability and employs a linear model to test inherent non-linear relations. Wicherts (2017) showed that this method can provide correlations far exceeding r =0.44 in cases where the group differences cannot possibly be on g because the items measure different traits across the groups. The psychometric problems with their method cast serious doubts on te Nijenhuis et al .'s conclusions concerning the role of g in the studied group difference in cognitive test performance.